Entrepreneurship Programs in Developing Countries : A Meta Regression Analysis - Cho, Yoonyoung; Honorati, Maddalena (2013)
Fostering entrepreneurship is widely perceived to be a critical policy agenda to expand employment and earning opportunities and to reduce poverty. Sound macroeconomic conditions and business environment including infrastructure, regulation, and legal environment have typically been emphasized to increase entrepreneurial activities and create jobs. While these remain relevant, in developing countries, increasing attention is being paid to the role of labor policies that aim to reduce constraints and enhance productivity among the self-employed and small-scale entrepreneurs. The next section describes the procedure for constructing data and discusses main features of the entrepreneurship programs in our sample studies. Section three presents a standardization and estimation strategy using Meta regressions and discusses methodology. Section four then discusses the main findings of the Meta analysis. Finally, Section five concludes the study.